Selection of genotypes of Coffea arabica for drought tolerance based on anatomical and physiological characteristics - Cyntia Stephânia dos Santos; Ana Flávia de Freitas; Glauber Henrique Barbosa da Silva; Maria Clara dos Santos Tavares; Milene Alves de Figueiredo Carvalho; Meline de Oliveira Santos; Gladyston Rodrigues Carvalho; Vânia Aparecida Silva (Rodriguésia)
Abstract Climate change affects crop productivity, with forecasts for the coming years pointing to increased temperatures and changes in rainfall distribution. This paper aimed to identify genotypes of Coffea arabica that are potentially drought-tolerant. Seven germplasm genotypes of Timor Hybrid were evaluated in comparison to two cultivars considered as sensitive and drought-tolerant. These were submitted to two water treatments, the first maintaining water availability and the second with complete suspension of irrigation. The physiological characteristics analyzed were gas exchange and predawn leaf water potential. For leaf anatomy, characteristics of the leaf lamina, conductive vessels and stomata were evaluated. It was found that some genotypes were able to maintain gas exchange even under low water availability. For these genotypes, the analysis of leaf anatomy presented an increase in cuticle thickness on the adaxial face, in the relationship between polar and equatorial diameters of stomata, in addition to a lower vulnerability index. A positive relationship was observed between adaxial phase cuticle thickness and water use efficiency. The Timor Hybrid UFV 377-21, UFV 376-31 and the cultivar IPR100 were the highlights among the genotypes analyzed, which presented adaptations that allowed the maintenance of the hydric status in the initial development phase.